Takotsubo cardiomyopathy, acute myocardial infarction and dyslipidaemia: a comparison of studies. (1st December 2016) - De Giorgi, Alfredo; Guarino, Matteo; Boari, Benedetta; Cappadona, Rosaria; Maietti, Elisa; Fabbian, Fabio; Manfredini, Roberto
Abstract: Background : Takotsubo cardiomyopathy (TTC) and acute myocardial infarction (AMI) share similar clinical presentation and risk of death, although one of the most important differences is the absence of obstructive coronary disease in TTC. We analysed the available literature and evaluated the prevalence of dyslipidaemia in patients with TTC compared with patients with AMI. Methods : A MEDLINE literature search to identify relevant papers focused on TTC and AMI was performed, evaluating the prevalence of dyslipidaemia in both groups. Systematic reviews, meta-analyses, controlled trials, cohort studies and case-control studies were considered for inclusion. We focused on studies reporting precise data on the prevalence of dyslipidaemia for both groups. Results : Out of a total of 511 articles found, 207 case reports, 24 comments, 56 letters and 57 articles in languages other than English were excluded. Of the remaining 167 papers, 23 articles providing the required information were selected. They included and compared 2247 TTC and 19, 843 AMI patients. Cases with dyslipidaemia were 734 (32.7%) in the TTC group and 6592 (33.2%) in the AMI group. Conclusions : Patients with TTC showed a prevalence of dyslipidaemia comparable with that of patients with AMI. The prevalence of dyslipidaemia and clinical outcome in TTC and AMI may represent unrelated issues. It is likely that for TTC patients, other conditions and comorbidities, rather than dyslipidaemia alone and/or other established risk factors, are responsible for a risk of death comparable with that of AMI.